Automatisation developments on ESRF-EBS BM05 beamline - Fabien Léonard; Florian Jürries; Elodie Boller (e-Journal of Nondestructive Testing)
X-ray computed tomography and radiography imaging are currently the second most exploited technique at the European Synchrotron Radiation Facility (ESRF) for commercial services. To maximise the growth, the beamlines must be flexible enough to accommodate a wide range of materials and sample sizes, whilst conserving operational efficiency and ensuring reliable and high-quality imaging outcomes. In this paper, we present some of the latest developments on the BM05 tomography beamline from the ESRF in terms of automatisation, processes, and procedures that ensure an efficient and robust operation of the beamline. For all users, the automatisation developments are focused on being able to set-up the beamline in a pre-defined state as easily and quickly as possible, so that time consuming user interventions (and potential mistakes) are minimised. For academic users, a graphical user interface (GUI) called Daiquiri tomo has been developed as a simple tool for non-experts to be able to perform most of their scanning operations in a user-friendly and efficient fashion, with minimum support from beamline scientists. For commercial users, a robotic sample changer has been assembled to be able to scan series of up to 45 samples, and maximise usage of night shifts. Overall, those improvements are key in reaching operational excellence and X-ray computed tomography and radiography imaging are projected to rival macromolecular crystallography (MX) as the first technique for commercial services at ESRF by the end of 2025.